2022
DOI: 10.3389/fcell.2022.842835
|View full text |Cite
|
Sign up to set email alerts
|

The Role of m6A Regulator-Mediated Methylation Modification and Tumor Microenvironment Infiltration in Glioblastoma Multiforme

Abstract: N6-methyladenosine (m6A) RNA methylation is an emerging epigenetic modification in recent years and epigenetic regulation of the immune response has been demonstrated, but the potential role of m6A modification in GBM tumor microenvironment (TME) cell infiltration and stemness remain unknown. The m6A modification patterns of 310 GBM samples were comprehensively evaluated based on 21 m6A regulators, and we systematically correlated these modification patterns with TME cell infiltration characteristics and stemn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…It has been shown that both METTL3 and METTL14 contribute to the development and tumorigenesis of human glioma stem cells (GSCs), and METTL3 overexpression or suppression of FTO inhibits GSC self-renewal and growth ( 20 ). Our previous study also observed an association between anti-PD-L1/PD-1 treatment response and m6A modification patterns, confirming that m6A modification patterns in GBM affect the infiltration of immune cells in the GBM microenvironment ( 6 ).…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…It has been shown that both METTL3 and METTL14 contribute to the development and tumorigenesis of human glioma stem cells (GSCs), and METTL3 overexpression or suppression of FTO inhibits GSC self-renewal and growth ( 20 ). Our previous study also observed an association between anti-PD-L1/PD-1 treatment response and m6A modification patterns, confirming that m6A modification patterns in GBM affect the infiltration of immune cells in the GBM microenvironment ( 6 ).…”
Section: Introductionsupporting
confidence: 73%
“…Our previous work demonstrated the mechanism of m6A methylation modification related to the regulation of TME immune cell infiltration, stemness and biological processes in GBM ( 6 ). We found that the copy number variations status of the four m6A regulators YTHDC1, ALKBH5, FTO, and METTL3 were correlated with the development of GBM ( 6 ). Zhu et al.…”
Section: M6a Modification and Glioblastomamentioning
confidence: 99%
See 3 more Smart Citations